2014
DOI: 10.1002/dev.21208
|View full text |Cite
|
Sign up to set email alerts
|

Placentophagia in weanling female laboratory rats

Abstract: Placentophagia is common in parturient mammals and offers physiological and behavioral advantages for mothers. In natural environments, weanlings are often present during the birth of younger siblings, but it is unknown if weanling rats are placentophagic or prefer placenta over other substances. To examine this, primiparous rats were remated during the postpartum estrus and weanling females remained in the nest during their mother’s next parturition. Continuous observation revealed that 58% of weanlings were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…Similar findings were found by Melo and González-Mariscal [ 12 ]: they offered rabbits ( Oryctolagus cuniculus ) liver and placenta during parturition and observed that the behavior of ingesting placenta increased in this state up to practically a 100% frequency. In contrast, liver consumption was only 10%, compared to another physiological state [ 11 ].…”
Section: Factors That Explain the Phenomenonmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar findings were found by Melo and González-Mariscal [ 12 ]: they offered rabbits ( Oryctolagus cuniculus ) liver and placenta during parturition and observed that the behavior of ingesting placenta increased in this state up to practically a 100% frequency. In contrast, liver consumption was only 10%, compared to another physiological state [ 11 ].…”
Section: Factors That Explain the Phenomenonmentioning
confidence: 99%
“…Placentophagia has been thoroughly studied, primarily in mice ( Peromyscus californicus ) [ 9 ], hamsters ( Phodopus campbelli ) [ 10 ], rats ( Mus musculus ) [ 11 ], rabbits ( Oryctolagus cuniculus ) [ 12 , 13 ], ungulates [ 14 , 15 ], and carnivores [ 16 ], and regularly occurs in all nonhuman primate species [ 17 , 18 , 19 ]. In contrast, it is assumed that traditionally, women did not carry out this practice for socio-cultural reasons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data are very consistent with those of Uriarte et al (). They also extend upon them by suggesting that the reduction in anxiety is not due to other events experienced by older pups raised in overlapping litters, such as the endocrine consequences of suckling on a pregnant dam (Koldovsky & Thornberg, ; Melo, ), sharing in placentophagia with their mothers during the second parturition (Harding & Lonstein, ), or the continued interaction with the mother past typical laboratory weaning age (Wu et al, ). Our results also show that the juvenile alloparental experience can be as short as three days and still reduce aspects of females’ later anxiety behavior.…”
Section: Discussionmentioning
confidence: 91%
“…These manipulations of the early postnatal environment involve additional maternal stimulation of the pups, which may underlie the later changes in postpartum anxiety during adulthood. In addition, because most juvenile females in overlapping litters would naturally join their mother in ingesting the placenta of the younger litter while she gives birth to them (Harding and Lonstein, 2014), there might be hormonal or other factors ingested by the periweanlings that can influence their adult postpartum affective behaviors.…”
Section: Accepted Manuscriptmentioning
confidence: 99%